How Accurate Are Private Sector Forecasts : Cross-Country Evidence From Consensus Forecasts of Output Growth - Loungani, Prakash (IMF Working Papers; Working Paper ;, 2000)
This paper evaluates the performance of Consensus Forecasts of GDP growth for industrialized and developing countries from 1989 to 1998. The questions addressed are (1) How do forecast errors differ across industrialized and developing countries? (2) How well do forecasters predict recessions? (3) Are forecasts efficient and unbiased? (4) How does private sector performance compare with that of international organizations? (5) Is forecaster discord a reliable predictor of forecast accuracy? Two key results emerge. First, the record of failure to predict recessions is virtually unblemished. Second, there is high degree of similarity between private forecasts and those of international organizations.